Early Information About Bio-physical Quality of Seaweed Culture (Eucheuma cottonii) in Waworada Bay, Bima Regency - Sirajuddin, M. (Indonesian Society of Scientific Aquaculture (ISSA), 2009)
One of the potential areas for developing mariculture in West Nusa Tenggara Province is Waworada Bay of Bima Regency. The aim of this research was to find out the early information about bio-physical quality in Waworada Bay for sustainable development of seaweed culture. PCA (Principal Components Analysis) was used to explore the characteristic distribution of biophysics parameters, and then explore the relationship between seaweed production and carragenan content with biophysics parameters. GIS analysis was also applied to determine the suitable area for seaweed culture. PCA analysis shows that the main parameters of growth seaweed culture was light penetration, water current, water deepness, pest, salinity, nitrate and Pb. As additional parameters were temperature, COD, DO, Phosphate, and pH. Biophysics parameters were found to have very important relationship with seaweed growth, production and carragenan content. Based on GIS analysis, 11,128 ha of 11,135 ha was very ideal for seaweed culture, and the remaining was unsuitable for seaweed culture. Keywords: seaweed, Eucheuma cottonii, biophysics, PCA, GIS, Waworada Bay ABSTRAK Salah satu wilayah yang sangat potensial untuk pengembangan budidaya rumput laut di Nusa Tenggara Barat adalah Teluk Waworada Kabupaten Bima. Tujuan dari penelitian ini adalah untuk mengetahui kondisi awal kualitas biofisik Teluk Waworada untuk pengembangan budidaya rumput laut. PCA (Principal Components Analysis), digunakan untuk mengetahui distribusi karaktersitik parameter biofisik, hubungan antara parameter biofisik dengan produksi dan kandungan karaginan rumput laut dan penentuan parameter utama pengembangan budidaya rumput. Sedangkan untuk mengetahui kelayakan lokasi digunakan analisa GIS (Geografis Information System). Hasil analisa PCA menunjukan bahwa korelasi antara variable terpusat pada dua sumbu utama dengan kontribusi sebesar 79%. Parameter biofisik hasil penelitian ini sangat penting untuk pertumbuhan, produksi dan karaginan rumput laut. Hasil analisa GIS terdapat 11.138 ha 11.128 sangat sesuai dan 0.0007 yang tidak sesuai. Kata kunci: rumput laut, Eucheuma cottonii, biofisik, PCA, GIS, Teluk Waworada